Green HRM as a Driver of Hotel Employee Performance: The Intervening Role of Environmentally Friendly Workplace Behaviors - C Susmono Widagdo; Dyah Palupiningtyas; Krisnawati Setyaningrum Nugraheni; Aletta Dewi Maria; Ray Octafian (Management Dynamics: International Journal of Management and Digital Sciences, 2024)
This study examines the relationship between Green Human Resource Management (Green HRM), Pro-Environmental Behavior (PEB), and Employee Performance in the hospitality industry. Using data collected from 265 employees across 12 star-rated hotels in Semarang that have implemented green hotel practices, this research employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed hypotheses. The findings reveal that Green HRM positively influences both PEB (β = 0.627) and Employee Performance (β = 0.341). Furthermore, PEB positively affects Employee Performance (β = 0.396) and partially mediates the relationship between Green HRM and Employee Performance. Demographic factors, including age, education level, and tenure, moderate several relationship paths, suggest the importance of a differentiated approach in Green HRM implementation. Among Green HRM dimensions, Training and Development and Employee Involvement have the strongest effect on PEB, while Performance Management and Reward Systems most directly influence Employee Performance. These results provide empirical evidence that integrating environmental sustainability into HR practices benefits not only environmental outcomes but also enhances employee performance, creating a win-win situation for hotels in their pursuit of competitive advantage while meeting environmental responsibilities.